2021
DOI: 10.1200/jco.2021.39.15_suppl.10012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ctDNA levels after MIBG therapy in patients with relapsed or refractory neuroblastoma.

Abstract: 10012 Background: Circulating tumor DNA (ctDNA) is detectable in children with neuroblastoma. Less is known about how levels change during treatment and the implications of these changes. We evaluated ctDNA pre- and post- 131I-metaiodobenzylguanidine (MIBG) therapy. Methods: We utilized plasma samples from NANT11-01 (NCT02035137), a multi-center, open label, randomized phase II clinical trial evaluating MIBG with or without radiation sensitizers for patients with relapsed or refractory neuroblastoma. Plasma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…72,73 ctDNA concentration in plasma or serum from patients with NB can be used for monitoring clinical response and detecting early tumor occurrence. [74][75][76] Apart from cfDNA level, recent studies have also demonstrated the detection of various NB-specific genetic and epigenetic alterations in cfDNA from patients during the course of disease, including MNA, 71,[77][78][79] ALK amplification or mutation, 78,80 segmental chromosome alterations (17q gain, 11p loss), [80][81][82] and epigenetic modifications (hypermethylation of RASSF1A and DCR2, 5-hydroxymethylcytosine profiles). 74,[83][84][85] In addition to the identification of canonical NB-specific genome alterations by PCR-based methods (qPCR, ddPCR), comprehensive genomic analysis methods including targeted panel sequencing of cancerassociated genes, whole-exome sequencing, and wholegenome sequencing allow detailed characterization of patient-specific ctDNAs and provide insights into its prognostic and surveillant utilities.…”
Section: Clinical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…72,73 ctDNA concentration in plasma or serum from patients with NB can be used for monitoring clinical response and detecting early tumor occurrence. [74][75][76] Apart from cfDNA level, recent studies have also demonstrated the detection of various NB-specific genetic and epigenetic alterations in cfDNA from patients during the course of disease, including MNA, 71,[77][78][79] ALK amplification or mutation, 78,80 segmental chromosome alterations (17q gain, 11p loss), [80][81][82] and epigenetic modifications (hypermethylation of RASSF1A and DCR2, 5-hydroxymethylcytosine profiles). 74,[83][84][85] In addition to the identification of canonical NB-specific genome alterations by PCR-based methods (qPCR, ddPCR), comprehensive genomic analysis methods including targeted panel sequencing of cancerassociated genes, whole-exome sequencing, and wholegenome sequencing allow detailed characterization of patient-specific ctDNAs and provide insights into its prognostic and surveillant utilities.…”
Section: Clinical Settingmentioning
confidence: 99%
“…Elevated total cfDNA levels in the plasma indicated a heavier tumor burden, associated with tumor staging, MYCN amplification (MNA), primary tumor sites, and tumor metastasis 72,73 . ctDNA concentration in plasma or serum from patients with NB can be used for monitoring clinical response and detecting early tumor occurrence 74–76 . Apart from cfDNA level, recent studies have also demonstrated the detection of various NB‐specific genetic and epigenetic alterations in cfDNA from patients during the course of disease, including MNA, 71,77–79 ALK amplification or mutation, 78,80 segmental chromosome alterations (17q gain, 11p loss), 80–82 and epigenetic modifications (hypermethylation of RASSF1A and DCR2 , 5‐hydroxymethylcytosine profiles) 74,83–85 .…”
Section: Ctcs Versus Ctdna In the Clinical Settingmentioning
confidence: 99%